This Way to the Ovens, Señoras y Señores: Holocaust Cartoons in Latin America. Issue 3 (30th May 2019) - Stavans, Ilan
ABSTRACT: An exploration of the world of syndicated cartoons, comics, and other 'humor' illustrations that address the Holocaust and fall within the purview of anti-Semitism and anti-Zionism from the last third of the twentieth century to the present throughout Latin America, with an emphasis in Argentina, Mexico, and Spain.